Motivation of elderly worker (ELDERLY) in market Bandar Buat in Lubuk Kilangan subdistrict - Angreini, Reni; Ahmad, Ridwan; Zahara, Leni (Pendidikan Geografi, 2013)
This research has alms to know, analyze and disiuss about motivation or elderly worker (ELDERLY) in from : 1) erderly education level 2) elderly earnings level and 3) elderly healths level.This research is a qualitative research with using interview technique to answer this problems used secondary data and primary data. Secondary data obtained from related parties, whereas primary data collected through observation, interview, discusion with informant and photoswerw take in the field. Informants determination as many 10 elderly people who are in the area of Bandar Buat market, Lubuk Kilangan subdistrict.The result of research showed that : 1). Elderly education level still low on an average, because of limitedness cost in their period of school ago, so that they graduate from elementary school on an average 2). Motivation to work from elderly in this market is very high with desire and hobby are owned by elderly 3). Elderly earnings level on an average to complete daily necessity of life and can not ascertained to complete a better necessity of life from now, because nominally their incomes lets than Rp.200.000 on an average 4). Elderly healthis condition not so good, because their incomes not sufficient to complete nurssing needs.Â